Topical combination of meldonium and N‐acetyl cysteine relieves allodynia in rat models of CRPS‐1 and peripheral neuropathic pain by enhancing NO‐mediated tissue oxygenation. Issue 5 (27th January 2020) - Fulas, Oli A.; Laferriere, Andre; Stein, Robin S.; Bohle, D. Scott; Coderre, Terence J.
Abstract: Local microvascular dysfunction and consequent tissue ischemia/hypoxia contribute to the symptoms of complex regional pain syndrome (CRPS) and peripheral neuropathic pain. As nitric oxide (NO) is a key regulator of microvascular blood flow, compounds that increase it are potentially therapeutic for these pain conditions. This led us to hypothesize that the topical administration of drugs that modulate local tissue NO levels can alleviate the pain of CRPS and peripheral neuropathic pain. We investigated the anti‐allodynic effect of a combination of two NO‐modulating drugs: meldonium and N‐acetylcysteine (NAC). An equimolar topical formulation of the two drugs was tested on chronic post‐ischemic pain (CPIP), a rat model of CRPS, as well as chronic constriction injury (CCI) of the sciatic nerve and chemotherapy‐induced painful neuropathy (CIPN), rat models of peripheral neuropathic pain. Topical meldonium‐NAC produced significant anti‐allodynia in CPIP, CCI, and CIPN rats. Moreover repeated application of topical meldonium‐NAC produced an increase in the duration of anti‐allodynia in the CPIP and CCI rats. While pre‐treatment with an NO synthase inhibitor attenuated the anti‐allodynic effects of meldonium‐NAC, 30‐min hyperbaric oxygen treatment combined with a non‐effective dose of meldonium‐NAC produced significant anti‐allodynic effects in CPIP rats. Both experiments implicated NO in the drug combination's anti‐allodynic effects. To ascertain the role played by changes in local tissue NO, we performed a quantification of plantar muscle NO in CPIP rats after hind paw topical treatment with meldonium‐NAC and revealed significantly increased plantar muscle NO levels in drug‐treated rats. The drug combination also reversed the reduction in tissue oxygenation normally observed in CPIP hind paws. In addition to introducing a novel topical treatment for mechanical allodynia in CRPS and peripheral neuropathic pain, this work showcases the analgesic potential of locally targeting microvascular dysfunction and tissue ischemia/hypoxia in these conditions, with emphasis on the role of NO. Abstract : Spontaneous pain and chronic mechanical hypersensitivity of both complex regional pain syndrome (CRPS) and peripheral neuropathic pain (PNP) depend partly on microvascular injury following ischemia reperfusion injury of either multiple limb tissues (CRPS) or an injured nerve (PNP). Microvascular dysfunction in these syndromes is maintained by reduced vasodilatory nitric oxide (NO), which contributes to vasospasms, poor blood flow, and reduced tissue oxygenation (O2 ). Topical treatment with a combination of meldonium and N‐acetylcysteine (NAC) reduced mechanical hypersensitivity in animal models of CRPS and PNP by increasing NO, that produced vasodilation and increased tissue O2 .